Analisis Perbedaan Tingkat Pemahaman Pajak dan Moral Pajak pada Generasi Milenial dan Generasi Z Indonesia - Mila Rahmadani; Eka Fauzihardani (Universitas Negeri Padang, 2024)
In 2045 Indonesia will have a demographic bonus phenomenon dominated by productive citizens, they are the millennial generation and generation Z, that will increase the number of taxpayers and increase tax revenue. So, our must know about the basic factors that influence voluntary tax compliance, namely tax understanding and tax morals owned by millenials and generation Z as future taxpayers. This study aims to examine the level of tax understanding and tax morale of millenials and generation Z, and to examine which generation has a better level of tax understanding and tax morale. This research is a comparative study using a quantitative approach. Data of this study are primary data. Data collection is by using closed-ended questionairres. The samples in this study were millennials and generation Z who had studied, read, heard or found out information about taxation. The sampling technique used purposive sampling technique. The hypothesis in this study was tested using a two-sample mean difference test (Independent sample t test) with IMB SPSS 25. The results showed that the millennial generation's tax understanding and tax morale were better than those of generation Z. Then for each generation, the millennial generation's tax understanding is better (higher) compared to their tax morale. Likewise with generation Z where generation Z's tax understanding is better (higher) than their tax morals.